Mikrobrowary jako element rozwoju regionalnego w Polsce i na Podkarpaciu - Niemczyk, Lesław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
In recent years, a boom in the micro-brewery sector has been observed in the world. This boom was launched in the US and UK. Nowadays, it is clearly outlined in Poland as well. This phenomenon is referred to as the “craft beer revolution”. The article attempts to define the essence of this phenomenon. The aim of the study is to analyze the essence of micro-breweries functioning in Poland and Podkarpacie region in the context of regional development. The research method used are as follows: elements of the historical method, elements of the semantic method, deduction, analysis of the stakeholders of the enterprise. From the studies conducted, it can be concluded that the development of micro-brewers is conducive to regional development. At the same time, data show that the Podkarpacie region is not giving away to other regions of the country in the sphere of brewing development.
Keywords: Micro-Breweries; Regional Development; Craft Beer Revolution; Podkarpackie Region